Meta-Analysis: Association of Obesity with Incidence of Polycystic Ovarian Syndrome (PCOS) - Tuminah Tuminah; Cusmarih Cusmarih (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Polycystic Ovary Syndrome (PCOS) is one of the disorders that often attacks women that cause difficulty obtaining pregnancy. PCOS causes 5-10% of women of reproductive age to become infertile. In Indonesia itself, the exact incidence of PCOS is unknown. Most people with Polycystic Ovary Syndrome (PCOS) do not know that they have the syndrome. This cannot be separated from precipitating factors, one of which is obesity or high body mass index. The purpose of this meta-analysis was to estimate the strength of the effect of obesity on the incidence of PCOS. This study is a systematic review and meta-analysis. Primary data is retrieved through the electronic databases PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords "obesity AND risk factor AND PCOS", "body mass index" AND "polycystic ovary syndrome". Articles taken between 2013-2023. Statistical analysis was performed using the RevMan 5.3 application. 6 articles qualified quantitatively for analysis. Increased body mass index or obesity, especially the abdomen, will increase the risk of PCOS 1.99-fold compared to women who have a normal body mass index and are statistically significant (OR 1.99; 95% CI: 1.79 – 2.20; p value < 0.001). Body mass index or obesity, especially the abdomen, will increase the risk of PCOS 1.99 times compared to women who have a normal body mass index.